Elementary students’ attitudes towards STEM and 21st-century skills - Riki Perdana; An-Nisa Apriani; Rino Richardo; Endi Rochaendi; Chahya Kusuma (International Journal of Evaluation and Research in Education (IJERE), 2021)
Science, Technology/Engineering and Math (STEM) and 21st-century learning are very important to be applied to all students starting from their early age, including at the elementary school level. This study aimed to describe students' attitudes towards STEM and 21st-century skills according to gender and education level. This research was descriptive quantitative by explaining and comparing the results of the questionnaires given to students. Student attitudes were described based on domain of STEM, 21st-century skills, gender, and student grade level. The respondent of this study was 130 elementary students who were obtained randomly from one of the elementary schools in Yogyakarta, Indonesia. The results showed that based on the science domain, the mean score of the students was 3.23 (moderate) while mathematics domain obtained was 3.21 (moderate); technology/engineering domain obtained was 3.68 (moderate) and 21st-century skill domain obtained was 3.65 (moderate). According to gender, there was a significant difference between the attitudes of male and female students towards STEM and 21st-century skills. However, there was no significant difference based on the grade of students. Based on these findings, it is suggested that teachers or policymakers should have comprehended the student attitudes before implemented the STEM-based learning and 21st-century skills. These findings can be used to create STEM and 21st-century learning.